GGV formula attenuates CCl4-induced hepatic injury in mice by modulating the gut microbiota and metabolites - Wang, Yifang; Zhang, Yihua; He, Yinting; Zhang, Shixun; Huang, Bo; Wang, Yarong; Lin, Weibin; Xiao, Weicheng; Zou, Zhenzhuang; Cui, Guozhen (Frontiers in Nutrition, 2025)
BackgroundLiver disease is a global health issue requiring effective therapeutic interventions. Although the individual hepatoprotective properties of glutathione, Ganoderma lucidum extract, and vitamin C are well-documented, their combined effects remain to be elucidated.ObjectiveThis study aims to investigate the hepatoprotective potential of a functional food formula named GGV to mitigate acute liver injury induced in mice.MethodsGGV was orally administered in a mouse model of carbon tetrachloride (CCl4)-induced acute liver injury. Liver function was assessed by measuring serum and hepatic biomarkers. Gut microbiota composition and diversity were evaluated using 16S rRNA gene sequencing. Serum metabolomic profiling was conducted using UPLC-Q/TOF-MS.Results and conclusionGGV administration significantly ameliorated CCl4-induced liver dysfunction, exhibiting greater efficacy than its individual components. Gut microbiota analysis revealed that GGV treatment restored the microbial diversity and composition disrupted by CCl4 exposure. Metabolomic profiling further indicated that GGV normalized phospholipid, fatty acid, and bile acid levels. Correlation analysis identified specific microbial genera associated with serum bile acid profiles, suggesting that the hepatoprotective effects of GGV are mediated through modulation of gut microbiota composition and metabolites. Taken together, these findings support the potential of GGV as a promising dietary intervention for promoting liver health through the liver-microbiota-gut axis.